Digital Poetics : Hypertext, Visual-Kinetic Text and Writing in Programmable Media - Glazier, Loss Pequeño (Book collections on Project MUSE., 2013)
In this revolutionary and highly original work, poet-scholar Glazier investigates the ways in which computer technology has influenced and transformed the writing and dissemination of poetry. In Digital Poetics, Loss Pequeño Glazier argues that the increase in computer technology and accessibility, specifically the World Wide Web, has created a new and viable place for the writing and dissemination of poetry. Glazier's work not only introduces the reader to the current state of electronic writing but also outlines the historical and technical contexts o.